Cork oak (Quercus suber L.) wood growth and vessel characteristics variations in relation to climate and cork harvesting - Leal, Sofia (2008)
Variations in tree ring growth of Quercus suber L. were analysed using dendrochronological techniques on cork oak discs from trees harvested in the cork producing region of Alentejo, Portugal. A tree-ring chronology containing a strong common signal and covering the period from 1970 to 1995 was build for ca. 30-year-old cork oaks never submitted to cork harvesting using 14 trees that crossdated satisfactorily out of 30 sampled trees. The tree ring indices correlated positively with September temperature (r = 0.48, P < 0.05) and very strongly with precipitation totals from previous October until current February (r = 0.82, P < 0.001) showing that the water stored in the soil during the autumn and winter months prior to the growing season has a primordial effect on the growth of the given season. The effects of cork harvesting were analysed by comparing mean ring width, mean annual vessel area, vessel density (n vessels/mm2), and vessel coverage (percentage of transverse surface occupied by vessels) between three mature cork oak trees and three young trees, for the period from 1987 to 1996, corresponding to the growth between two consecutive cork removals in the case of mature trees. In 1988, 1989 and 1996 (corresponding to the first and second years after cork removal, and 1996 to a year of cork removal), the ratios between ring widths of young versus mature trees was twice that for the rest of the period. However, an effect of cork removal indicated by eventual alterations in vessel size and distribution in the wood rings corresponding to the years 1988, 1989 and 1996 in the mature cork oaks was not observed